Research and Analysis of the Energy Saving Pulley Reducer - Fan Shiyao; Ren Xiaoming (Jixie chuandong)
In order to solve the problem of existing beam pumping unit reducer,the belt transmission mechanism is difficult to meet the long stroke and low speed,the contradiction of the energy requirements and form a complete set of small power motor,and the start from zero and real- time detection of load records can be carried out. An energy- saving pulley gear reducer of beam pumping unit used for oilfield is developed.